(untitled) (Raparin Journal of Humanities (RJH), 2025)
Sematic studies are various and diverse, given the different perspectives on the lexical material under investigation, ranging from phonetics to morphology to syntax. Certainly, meaning changes with variations in grammatical attributions. In this study, we have examined the changes that occur in sentence meaning. There were 25 roots that began with the letter alif. We analyzed changes in meaning depending on whether the predicate or the subject was rational or irrational, male or female, child, or adult, singular or plural. This was done by examining the derivatives of these roots and their occurrences in sentences, which were over two hundred examples in total. It was confirmed that a complete separation between linguistic levels is nearly impossible. Since information should not be redundantly repeated in different forms, these levels must be intertwined, with some falling under others. The findings show that the most significant factor influencing meaning change is a shift in the subject, followed by a change in the object. Changes in the subject had effect on meaning depending on whether it was rational or irrational, masculine or feminine, an animal, plant, place, or other entity. Equally, changes in the object, upon which the verb is applied, followed the same patterns as those seen in the subject. Taking into consideration the complexity and variety of Arabic sentence structures, in the third part we compiled examples where meaning changed, sometimes because of the subject and due to the object in other occasions.